Pharmacokinetics and safety of MP-376 (levofloxacin inhalation solution) in cystic fibrosis subjects - Geller, David E; Flume, Patrick A; Griffith, David C; Morgan, Elizabeth; White, Dan; Loutit, Jeffery S; Dudley, Michael N (Antimicrobial agents and chemotherapy, 2011)
The pharmacokinetics and tolerability of nebulized MP-376 (levofloxacin inhalation solution [Aeroquin]) were determined in cystic fibrosis (CF) subjects. Ten CF subjects received single 180-mg doses of two formulations of MP-376, followed by a multiple-dose phase of 240 mg once daily for 7 days. Serum and expectorated-sputum samples were assayed for levofloxacin content. Safety was evaluated following the single- and multiple-dose study phases. Nebulized MP-376 produced high concentrations of levofloxacin in sputum. The mean maximum plasma concentration (C(max)) ranged between 2,563 and 2,932 mg/liter for 180-mg doses of the 50- and 100-mg/ml formulations, respectively. After 7 days of dosing, the mean C(max) for the 240-mg dose was 4,691 mg/liter. The mean serum levofloxacin C(max) ranged between 0.95 and 1.28 for the 180-mg doses and was 1.71 for the 240-mg dose. MP-376 was well tolerated. Nebulized MP-376 produces high sputum and low serum levofloxacin concentrations. The pharmacokinetics, safety, and tolerability were similar for the two formulations. MP-376 240 mg (100 mg/ml) is being advanced into late-stage clinical development.